Analisis Penjadwalan Produksi Dengan Metode MPS di PT. XYZ - silvia indah lestari (Jurnal Teknik, 2021)
In this era in the industrial sector, companies are competing with the other companies to get consumer trust. In addition to quality, product delivery is also in accordance with the predetermined schedule. The problem that exists at PT XYZ is the absence of a master production schedule as a basis for carrying out production activities which results in a lack of labor effectiveness and efficiency of working hours and also causes losses to the company. The method used in this research is forecasting (linear regression, moving average, double exponential smooting), and production scheduling (MPS). The purpose of this study is to analyze future demand and also create a master schedule for the production process. From the results of data processing, it is found that the appropriate forecasting method is linear regression with the smallest error rate. With the number of requests for 12 periods is 64778 units and the master schedule of product production at the beginning of the month is 8638 units and leaves less products to be produced to meet demand in the following month, which is 2947 units because production needs in that month are only 46870 units without overtime for workers.